Perbandingan Pendekatan Pedagogis dalam Pendidikan Islam: Dari Hafalan Tekstual Menuju Pembelajaran Berbasis Teknologi - Randi Saputra; Muhamad Afif Adnani; Sumiarti; Hamzah Irfanda (Laskar Karya, 2025)
This study analyzes the comparative teaching methods used in Islamic education, focusing on Islamic secondary schools and pesantren in Indonesia. Using a literature review approach, the research examines academic books, journal articles, and educational reports to identify the characteristics, strengths, and limitations of both traditional and modern teaching methods. The findings indicate that traditional methods are effective in strengthening students’ understanding of classical religious texts, cultivating discipline, and preserving Islamic scholarly traditions. However, these methods provide limited support for the development of critical thinking and creativity. In contrast, modern teaching methods enhance student motivation, active engagement, and the ability to relate learning materials to real-life contexts and the demands of the digital era, although their implementation is often hindered by technological limitations and teachers’ competencies. Overall, the study concludes that both methods demonstrate distinct forms of effectiveness and complement one another. Integrating traditional and modern approaches is therefore considered the most relevant strategy for developing Islamic education that is comprehensive, adaptive, and aligned with contemporary educational needs